Optimalisasi Strategi Komunikasi Digital Berbasis Konten Manyao untuk Membangun Loyalitas Pelanggan pada Oryza Pool and Café - Clio Ionakana; Yugih Setyanto (Kiwari, 2026)
This study explores the digital marketing communication strategy implemented by Oryza Pool and Café in strengthening customer loyalty amid increasing competition in the entertainment and culinary industry. The shift in consumer behavior toward digital content consumption requires businesses to optimize social media as their key communication channel. Oryza utilizes TikTok and Instagram as the primary platforms to communicate its brand identity, strengthen engagement, and attract new customers through visually appealing and culturally relevant content. Using a qualitative descriptive method, the research gathers data through in-depth interviews, observation of social media activities, and documentation of content interactions. The findings indicate that Oryza’s digital strategy focuses on understanding audience preferences, particularly through Manyao and Mandarin-themed music content, consistent posting schedules, humorous and educational content formats, and responsive communication with followers. These elements contribute significantly to increasing customer interaction, emotional attachment, and repeated visits. The study also shows that customer loyalty is strengthened through personalized communication, quick feedback handling, and creating a digital environment that encourages two-way interaction. Despite several challenges, such as platform algorithm changes and resource limitations, Oryza’s digital communication efforts remain effective in building long-term customer relationships. Penelitian ini mengkaji strategi komunikasi pemasaran digital yang diterapkan oleh Oryza Pool and Café dalam memperkuat loyalitas pelanggan di tengah persaingan industri hiburan dan kuliner yang semakin meningkat. Perubahan perilaku konsumen yang kini lebih mengandalkan media sosial menuntut pelaku bisnis untuk mengoptimalkan platform digital sebagai sarana komunikasi utama. Oryza memanfaatkan TikTok dan Instagram untuk memperkuat identitas merek, meningkatkan engagement, serta menarik pelanggan baru melalui konten visual yang menarik dan relevan dengan preferensi audiens. Penelitian ini menggunakan metode kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi aktivitas media sosial, dan dokumentasi interaksi digital. Hasil penelitian menunjukkan bahwa strategi digital Oryza berfokus pada pemahaman preferensi audiens, terutama melalui konten bertema Manyao atau musik Mandarin, pola unggahan yang konsisten, penggunaan konten humor dan edukatif, serta komunikasi yang responsif terhadap pengikut. Faktor-faktor ini berperan penting dalam meningkatkan keterlibatan pelanggan, membangun kedekatan emosional, dan mendorong kunjungan ulang. Selain itu, loyalitas pelanggan diperkuat melalui komunikasi yang personal, penanganan umpan balik yang cepat, dan penciptaan lingkungan digital yang mendorong interaksi dua arah.